Skin and wound care for individuals with graft versus host disease: a scoping review protocol. Issue 10 (8th October 2020) - Campbell, Jill; Gavin, Nicole; Button, Elise; Roberts, Natasha
Abstract : Introduction: Graft versus host disease (GVHD) is a major cause of morbidity and mortality following allogenic haematopoietic stem cell transplantation. It is an immunological reaction, involving many organs, leading to a wide range of clinical manifestations. Cutaneous manifestations are the most common sign of GVHD, as well as pain, vulnerability to infection and impaired quality of life. Despite the burdens that cutaneous GVHD presents for patients, their carers and the healthcare system, limited evidence is available to guide day to day supportive skin care and wound management. Our objective is to conduct a scoping review to map the evidence for skin and wound management and identify evidence-practice gaps for individuals with acute or chronic cutaneous GVHD. Methods and analysis: Our review will follow the scoping review methodological framework developed by Arksey and O'Malley and further refined by the Joanna Briggs Institute Scoping Review Methods Manual. Databases to be searched include; PubMed, EMBASE, PsycINFO, Cochrane Central Register of Controlled Trials, Cumulative Index to Nursing and Allied Health Literature, Web of Science and MEDLINE from 1970 to February 2020. Database searches will be supplemented with searches from relevant reference lists and grey literature. Descriptive statistical analyses will be performed. Ethics and dissemination: This scoping review does not require ethical approval. Findings will be disseminated through a peer-reviewed publication and conference presentation.